Learning to Read in Primary School Children with ASD and Intellectual Disabilities at the «Reading and Speech Development» Class - Tilkhonova K. A. (Moscow State University of Psychology and Education, 2018)
Children with autism and intellectual disabilities are able to master the reading skill in the conditions of systematic prolonged and adaptive learning. A teacher who realizes present task is important to know and take into account not only actual, but also potential mental abilities of the student. It is important for the teacher to apply new techniques of correctional pedagogy in his work, supplementing them with classical evidencedbased and reliable ones with the reliance on the zone of proximal development and on the principles of special pedagogy, in particular: developing education, accessibility, visibility, systemic and individuality. It is important for a teacher to remember that he is not only teaches, but also forming the personality of the child as a whole. The experience of teaching children with autism spectrum disorders and moderate intellectual disabilities to read who are educating in the school of the Federal Resource Center for Organization of Comprehensive Support to Children with Autism Spectrum Disorders is described.